A numerical study of the interhemispheric asymmetry of the equatorial ionization anomaly in solstice at solar minimum. Issue 9 (20th September 2016) - Dang, Tong; Luan, Xiaoli; Lei, Jiuhou; Dou, Xiankang; Wan, Weixing
Abstract: In this study, the mechanisms of interhemispheric asymmetry of the equatorial ionization anomaly (EIA) in June solstice at solar minimum were investigated through a series of simulations using the Thermosphere Ionosphere Electrodynamics General Circulation Model. Our results indicate that the transequatorial neutral wind is the main cause of the interhemispheric asymmetry. The transequatorial wind transports plasma from the summer hemisphere to winter hemisphere, leading to an enhancement in the winter EIA crest. Meanwhile, the ion production and loss are also important factors in producing the EIA asymmetry through photochemical processes. The longitudinal variations of the EIA interhemispheric asymmetry are also explored through imposing each term of ion continuity equation longitudinally independent. Our term analysis results suggest that the neutral wind variation dominates the longitudinal patterns of the interhemispheric asymmetry, while the E × B drift and photochemical process contribute less. Key Points: Transequatorial neutral wind is the major contributor to the EIA north‐south asymmetry The photochemical effect, associated with neutral composition and solar zenith angle, also contributes to the interhemispheric asymmetry Neutral wind dominates the longitude variation of the interhemispheric asymmetry while E × B drift and photochemical process contribute less